DNVF Memorandum - Ziele und Methoden bewegungsbezogener Versorgungsforschung - Gabrys, Lars; Schaller, Andrea; Peters, Stefan; Barzel, Anne; Berrisch-Rahmel, Susanne; Dreinhöfer, Karsten E.; Eckert, Katharina; Göhner, Wiebke; Geidl, Wolfgang; Krupp, Sonja; Lange, Martin; Nebel, Roland; et al. (Gesundheitswesen, 2024)
The DNVF Memorandum: Objectives and Methods of Physical Activity-Related Health Services Research summarizes, for the first time, the highly interdisciplinary and interprofessional field of physical activity-based health care in the German healthcare system. In addition to providing a conceptual framework and definition of key measures and concepts in physical activity-related health care research, existing research gaps and needs are identified, and methods for advancing this relatively young field of research are described. A particular focus of this study is the relevant outcome parameters and their standardized assessment using established and valid measurement tools. The memorandum aims to establish a general understanding of the complex subject of promoting physical activity and sports therapy in the context of healthcare, to give an impulse to new research initiatives, and to integrate the currently available strong evidence on the effectiveness of physical activity and exercise into healthcare.
CRIS-Team Scopus Importer:2024-09-27
Keywords: health; health care; physical activity; sport; therapie